Fevereiro 2022 (Abstracta, 2022)
Artigos publicados 2021 - P328-2021 à P370-2021Eventos publicados 2021 - P371-2021 à P372-2021Artigos publicados 2022 - P001-2022 à P033-2022Aceitos para publicação - A001-2022Defesas de Dissertações do IFGW - D001-2022 à D002-2022Defesas de Teses do IFGW - T001-2022 à T003-2022